Why government is the problem - Friedman, Milton (Stanford Stanford University, 1993)
The major social problems of the United States?deteriorating education, lawlessness and crime, homelessness, the collapse of family values, the crisis in medical care?have been produced by well-intended actions of government. That is easy to document. The difficult task is understanding why government is the problem. The power of special interests arising from the concentrated benefits of most government actions and their dispersed costs is only part of the answer. A more fundamental part is the difference between the self-interest of individuals when they are engaged in the private sector and the self-interest of the same individuals when they are engaged in the government sector. The result is a government system that is no longer controlled by "we, the people." Instead of Lincoln's government "of the people, by the people, and for the people," we now have a government "of the people, by the bureaucrats, for the bureaucrats," including the elected representatives who have become bureaucrats. At the moment, term limits apear to be the reform that promises to be most effective in curbing Leviathan.
Includes bibliographical references (p. 13).
Keywords: Free enterprise --United States